Acoustic emission uncovers thermal damage evolution of rock. (August 2020) - Zhang, Yuliang; Zhao, Gao-Feng; Li, Qin
Abstract: The thermal damage evolution of rock closely relates to many important scientific and engineering problems, such as the mechanisms of earthquake and the effective extraction of deep geothermal energy. However, there is lack of rational thermal damage evolution model, and the mechanisms of thermal damage are still unclear especially during cooling. By use of a specially designed acoustic emission (AE) test system, we explored the thermal damage evaluation in a rock and established a thermal damage evolution model which takes into account both heating and cooling processes. The mechanisms of rock damage caused by heating and cooling were analyzed by using a lattice spring model, and two different microstructural explanations were found, i.e. heterogeneous microstructure and microdefect structure. The damage evolution model can be used for more accurate modeling of these problems which involve rock thermal damage, such as induced seismic activity during deep geothermal exploration.